Bercocok Tanaman Jenis Hortikultura Memanfaatkan Limbah Plastik Untuk Mendukung Ekonomi Kerakyatan di Kelurahan Teluk Lerong Ulu - Sukariyan Sukariyan; Sri Ngapiyatun; Ernita Obeth; Arief Rahman; Humairo Aziza; Muhamad Yazid Bustomi; Sri Marlendi (Cv. Utility Project Solution, 2023)
Teluk Lerong Ulu Village has the highest population density compared to six other villages in Sungai Kunjang District, Samarinda City, and with dense settlements and minimal yard land. Innovation in cultivating horticultural crops can create sustainability, land use efficiency, meet daily food consumption, and increase the income level of residents if cultivated intensively. If horticultural crops are done intensively and become a culture in an environment, the environment becomes a beautiful and resilient environment. This community service program aims to be a form of synergy between the world of higher education and the community by increasing community insight and skills by cultivating horticultural crops in the yard using plastic waste. The method of implementing activities is in the form of extension activities and practices on the cultivation of horticultural crops by utilizing plastic waste as a place to grow crops. In this activity, the community can take advantage of a narrow yard by planting horticultural types and can use plastic waste as a planting medium, so that people will easily get food, especially vegetables needed by households, and can reduce household expenses in terms of buying vegetables.